Role of homoeopathy in Worm Infestation in Children - A Review (Homoeopathy for All, 2024)
Among children from developing countries, worm infestation in intestine is widely prevalent and it results in mal nutrition and development. It is estimated by WHO that infection with round worm (Ascarislumbricoides), whipworm (Trichuristrichiura) and hookworms (Ancylostomaduodenale and Necatoramericanus) with associated morbidity, affect approximately 250 million, 46 million and 151 million people, respectively.1 Intestinal parasitic infections are common among school age children.2,3 They cause nutritional deficiency and impaired physical developments. Due to nutritional deficiency, it results in cognitive dysfunction and learning disability.4 Homoeopathy has positive role in such worm infestations, both as stand-alone treatment and as supportive therapy in case of severe cases, along with other general hygienic measures. In this article, we have given an outline on the different aspects of the condition and glimpse of homoeopathic remedies useful in the treatment of worms.
Keywords: Ascarislumbricoides; Trichuristrichiura)